LITERASI LINGKUNGAN SISWA SMP: PENGETAHUAN EKOLOGI, KETERAMPILAN KOGNITIF, SIKAP PEDULI LINGKUNGAN, DAN PERILAKU TANGGUNG JAWAB - Devi Khoirunnisa; Yulianti Yusal; Ratna Wahyu Wulandari (Ikatan Keluarga Alumni FKIP Universitas Tanjungpura, 2023)
This study aims to determine how the level of environmental literacy of students and how the level of environmental literacy of students in the aspects of ecological knowledge, cognitive skills, environmental care attitudes, and environmentally responsible behavior. The samples in this study were SMPN 2 Kandangan class VIII students totalling 63 students. Data collection techniques in this study used environmental literacy tests to students. The environmental literacy test in this study uses environmental literacy test questions that adapt from the Middle School Environmental Literacy Survey (MSELS) standard assessment. The results of the calculation of the average environmental literacy score for all students show 65.4%, which is in the sufficient category. If it is narrowed down based on four environmental literacy indicators, different average values are obtained, namely ecological knowledge of 69.44% (sufficient category), cognitive skills of 52.06% (insufficient category), environmental care attitudes of 67.19% (sufficient category), and environmentally responsible behavior of 62.54% (sufficient category). Based on the data obtained, the environmental literacy skills of SMPN 2 Kandangan students are in the sufficient category and the average level of environmental literacy of students in four aspects is also in the sufficient category